Composition and Diversity of Intestinal Microbiota in Colorectal Cancer and Potential Utilization in Diagnosis and Therapy - Darnindro, Nikko (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
Colorectal cancer is the third most common malignancy and the fourth most common malignancy causing death in the world. The development of colorectal cancer is influenced by several factors, including external, internal environmental, and genetic factors. One of the environmental factors recently known to be associated with colorectal cancer is gut microbiota. Generally, gut microbiota has various functions and is influenced by several factors, such as food, drugs, activities, habits, and diseases. Microbiota may become imbalanced, otherwise known as dysbiosis, which may lead to several changes and disturbances that can initiate the development of malignancy. There were differences in the composition and diversity of the types of microbiota in colorectal cancer patients. This difference has the potential to be used as a diagnostic marker and also the development of treatment in patients with colorectal cancer.Keywords: gut microbiota, colorectal cancer, diversity, abundance